Neighborhood and Efficiency in Manufacturing in Brazilian Regions: a Spatial Markov Chain Analysis - Daniela Schettini; Carlos Roberto Azzoni; Antonio Páez (European Regional Science Association (ERSA), 2010)
More competitive regions tend to present higher level of economic growth, with positive reflexes on social aspects. The different economic performances observed among regions are explained mainly by the spatial concentration of the economic activities. This paper aims to analyze the influence of space on the regional competitiveness behavior of the Brazilian manufacturing industry. In doing so, it uses a panel data of 137 mesoregions and industry sectors that are aggregated in four categories according to technology intensity, during 2000 to 2006. We apply the stochastic frontier of production methodology to obtain the measures of regional efficiency and the Markov spatial transition matrixes that analyze the dynamic of the transition of the regions among efficiency categories considering their local spatial context. We found evidences that there is a higher probability of the regions to become less competitive when the neighborhood is not considered. On the other hand, when considering spatial influences, we observed that the probability of a good neighborhood (more competitive) in stimulating the region's efficiency is higher than the probability of a bad neighborhood (less competitive) in lowering its efficiency. In other words, the pull effect of the neighborhood in the competitiveness of the Brazilian regions is stronger than the drag effect.
Keywords: 330